Internalisasi Nilai Etika Sosial Hindu Melalui Pendidikan Pasraman: Studi Di Pasraman Semara Ratih Buleleng - I Gd. Dedy Diana Putra (Jurnal Penelitian Agama Hindu, 2026)
Globalization and modernization have significantly affected the sustainability of social ethical values within Hindu society, particularly among the younger generation. This condition highlights the urgency of strengthening value-based education to reinforce ethical foundations in social life. This study aims to analyze the role of Pasraman Semara Ratih in Tukadmungga Village, Buleleng District, Buleleng Regency, in internalizing Hindu-based social ethical values. Employing a descriptive qualitative approach, data were collected through an extensive literature review of Hindu scriptures and relevant scholarly works, supported by in-depth interviews and participatory observation involving pasraman administrators, teachers, and students. The data were analyzed thematically through data reduction, data presentation, and conclusion drawing. The findings indicate that Pasraman plays a strategic role as a character education institution by internalizing core Hindu social ethical values, including Dharma (duty and social responsibility), Ahimsa (non-violence), Satya (truthfulness), Karuna (compassion), and Sewa (selfless service). These values are implemented through a holistic learning process and socio-religious practices grounded in the principle of Tri Kaya Parisudha. In conclusion, Pasraman functions as a moral stronghold and a preserver of Hindu social ethical values, contributing to the formation of a young generation that is ethically grounded, socially responsible, and capable of adapting to the dynamics of modern life.